Perfil clínico y epidemiológico del Síndrome nefrótico en niños del Hospital Belén de Trujillo. 2009 - 2019 - Villanueva Díaz, María Ysabel (2020)
Nephrotic syndrome is one of the most common types of kidney disease seen in children. It is characterized by massive proteinuria, hypoalbuminemia, and edema, although additionally some clinical features such as hyperlipidemia are usually also present. Although nephrotic syndrome occurs most often as a primary disorder in children, it can also be associated with a variety of systemic diseases. The possible consequences of nephrotic syndrome are hypovolemia, acute renal failure, hypercoagulation and infections, which must be prevented with proper and timely management. Advances in the treatment of nephrotic syndrome have decreased mortality from 50% to less than 3%. Objective: To describe the clinical and epidemiological characteristics of nephrotic syndrome in children at Hospital Belén de Trujillo during the period 2009 - 2019. Method: Retrospective descriptive observational study, using medical records of children of both sexes with nephrotic syndrome, selected from the criteria of inclusion and exclusion.